1) \(\sqrt{x^2-4x+5}+3=4x-x^2\)
2) \(4\sqrt{x^2-6+6}=x^2-6x +9\)
3) \(\sqrt{x^2-3x^3}+\sqrt{x^2-3x+6}=3\)
4) \(\sqrt[3]{2-x}=1-\sqrt{x-1}\)
Giải phương trình :
\(\left(\frac{8}{3}\right)^{x^2-x+1}\left(\frac{3}{5}\right)^{2x^2-3x+2}\left(\frac{5}{7}\right)^{3x^2-4x+3}\left(\frac{7}{2}\right)^{4x^2-5x+4}=210^{\left(x-1\right)^2}\)
\(3x^2+10x+\sqrt{3x+3}=x^3+26+\sqrt{5-2x}\)
\(x^3+3x^2-3\sqrt[3]{3x+5}+1-3x\)
\(3x^2+10x+\sqrt{3x+3}=x^3+26+\sqrt{5-2x}\)
giúp em với ạ
Giải phương trình :
\(2\left(2x^2-3x+1\right)^2-3\left(2x^2-3x+1\right)+1=x\)
Giải phương trình :
\(\left(x^2+3x-4\right)^2+3\left(x^2+3x-4\right)=x+4\)
Giải các phương trình :
a. \(\left|3x-2\right|=2x+3\)
b. \(\left|2x-1\right|=\left|-5x-2\right|\)
c. \(\dfrac{x-1}{2x-3}=\dfrac{-3x+1}{\left|x+1\right|}\)
d. \(\left|2x+5\right|=x^2+5x+1\)
\(\sqrt{4x+1}\) - \(\sqrt{3x-2}\) = x + \(\dfrac{3}{9}\)